Adrenaline-induced acute massive pulmonary oedema in the dog - Cheng, C. P. K. (1973)
Pericardiotomy followed by intravenous injection of adrenaline (1 mg/kg body weight) provides a reliable method for the production of acute massive lung oedema in the dog. The lung wet weight: heart wet weight ratio is found to be the best assessment of the degree of lung oedema. A ratio greater than two represents massive lung oedema.